Mixing Tube Length Effect on the Stability of Confined Swirling Partially Premixed Methane Flames off a Concentric Flow Conical Nozzle Burner. Issue 16 (10th December 2021) - Ahmed, Mahmoud M.A.; Birouk, Madjid
ABSTRACT: The effect of mixing tube length (partial premixing level) on the amplitude of coherent structures and acoustics, and stability of partially premixed flames (PPFs) of methane off a concentric flow conical nozzle (CFCN) swirl burner is experimentally investigated. The flowfield inside the quartz confinement is documented using particle image velocimetry (PIV), and coherent structures are captured using proper orthogonal decomposition (POD) technique. Acoustics measurements are performed using Bruel & Kjaer type 4189 microphone. Additionally, high-speed imaging and quantitative light sheet (QLS) techniques are used to qualitatively investigate the flow mixing characteristics. The results reveal that increasing partial premixing level significantly enhances flame stability. Compared to traditional dump burner/combustor, the present burner configuration promotes flame divergence with no outer recirculation zone (ORZ) and larger homogeneous and isotropic turbulent zone. More importantly, the results show that, in contrast to the traditional dump combustor, the use of a swirl in a CFCN burner makes it possible to sustain stable flame under ultra-lean conditions.